2001
DOI: 10.1152/ajpheart.2001.280.2.h591
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-enhanced ischemic preconditioning: adenosine receptor involvement during ischemia and reperfusion

Abstract: Adenosine-enhanced ischemic preconditioning (APC) extends the cardioprotection of ischemic preconditioning (IPC) by both significantly decreasing myocardial infarct size and significantly enhancing postischemic functional recovery. In this study, the role of adenosine receptors during ischemia-reperfusion was determined. Rabbit hearts (n = 92) were used for Langendorff perfusion. Control hearts were perfused for 180 min, global ischemia hearts received 30-min ischemia and 120-min reperfusion, and IPC hearts re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…These results in the human myocardium are supported by studies in other animal species [23] but contrast with the results reported by Leesar et al [24] in the vivo human heart and by McCully et al [25] in the isolated rabbit heart. In the study by Leesar et al [24] patients undergoing percutaneous transluminal coronary angioplasty were subjected to three 2-minute balloon inflations 5 minutes apart.…”
Section: Discussionsupporting
confidence: 58%
“…These results in the human myocardium are supported by studies in other animal species [23] but contrast with the results reported by Leesar et al [24] in the vivo human heart and by McCully et al [25] in the isolated rabbit heart. In the study by Leesar et al [24] patients undergoing percutaneous transluminal coronary angioplasty were subjected to three 2-minute balloon inflations 5 minutes apart.…”
Section: Discussionsupporting
confidence: 58%
“…However, other studies seem to favor the use of insulin to restore the preconditioning effect in hyperglycemic patients or animals [16, 17]. It is now well known that activation of adenosine A 1 receptors (A 1 R), either by ischemic preconditioning or by specific agonists, triggers the protective effect against myocardial ischemia/reperfusion injury [1824]. However, the role of acute hyperglycemia in blocking the A 1 R pathway is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This imbalance likely has an important role in the triggering mechanisms of ischemic and pharmacological preconditioning (35). Many studies suggest that mitochondrial ATP-sensitive K ϩ (K ATP ) channels open during brief ischemia and also play a key protective role in normothermic I/R injury (5,13,17,24,30,41). Opening of K ATP channels is believed to be a common mechanism of IPC because K ATP channel antagonists attenuate the protection of IPC and K ATP agonists mimic the protection of IPC (18,29).…”
mentioning
confidence: 99%